2022
DOI: 10.1108/jima-10-2021-0337
|View full text |Cite
|
Sign up to set email alerts
|

Promoting business zakah as a product of Islamic finance to fund social causes for well-being of the underprivileged: evidence from Bangladesh

Abstract: Purpose This study aims to look into the scope of exploring and promoting business zakah for the enhancement of the well-being of the underprivileged in society. Design/methodology/approach This is mainly a qualitative research conducted using both primary and secondary data. Primary data have been collected from 34 business entrepreneurs in Bangladesh through semi-structured in-depth interviews. The secondary data have been collected from annual reports with a view to calculating business zakah of five busi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 62 publications
1
24
0
5
Order By: Relevance
“…Business/corporate zakah is a recent addition to the zakah system. Many scholars (Al-Qardawi, 1999;Abdul Rahman, 2007;Sabiq, 1985;Muhammad, 1980;Saad et al, 2020;Hoque, 2022) and institutions (MASB, 2006) have conceived the concept though not widely promoted yet in the Muslim societies. As a result, literature on it is yet scanty.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Business/corporate zakah is a recent addition to the zakah system. Many scholars (Al-Qardawi, 1999;Abdul Rahman, 2007;Sabiq, 1985;Muhammad, 1980;Saad et al, 2020;Hoque, 2022) and institutions (MASB, 2006) have conceived the concept though not widely promoted yet in the Muslim societies. As a result, literature on it is yet scanty.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, literature on it is yet scanty. Hoque (2022) reported that a few business entrepreneurs in Bangladesh are aware of business zakah. Similarly, empirical evidence of business zakah is found in the context of a few countries such as Pakistan (Ahmad and Haq, 2021), Malaysia (Noor et al, 2017) and Indonesia (Alfitr and Samarinda, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations